The sanitation-health nexus - Zurbrugg, C.; Luthi, C.; Hung Nguyen-Viet (2012)
The Millennium Development Goal (MDG) target of halving the proportion of the population without sustainable access to basic sanitation by 2015 is still very far from being achieved. Much remains to be done particularly in Africa and Asia. Availability, accessibility, functionality, and correct and continued use and maintenance of sanitary facilities are key to sustainable improvements. Reasons for frequent failures of sanitation programmes are weak intersectoral collaboration, as well as inappropriate technical solutions that do not sufficiently consider aspects of local ownership and socio-economic, cultural, and political perspectives. Only improved practices and sustained use of improved facilities and services can lead to significant health and environmental outcomes. Integrative cross-sectoral planning of waste management is crucial in achieving a positive impact on both health and the environment. Recovery and reuse of resources from wastes while ensuring health safety, for example, can contribute to change and promote sustainable development. The links between health, waste, and the livelihood potential in waste are important elements in achieving equitable improvements that benefit the most vulnerable population segments.